ANALISIS PENGARUH RETURN ON ASSET (ROA) DAN NET PROFIT MARGIN (NPM) TERHADAP INCOME SMOOTHING (Studi Kasus Perusahaan Manufaktur yang terdaftar di BEI) - Iswandir Iswandir (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2018)
Company value can increase through financial performance, and performance is an important indicator to attract investors. Good performance is the greater the company's ability to provide returns as per investor expectations. One of the ratios used in assessing financial performance is Return on Assets (ROA) and Net Profit Margin (NPM). The effects of investor relations and management, causing an asymmetric relationship, management with high bonus expectations by increasing the company's earnings in a certain periodRegardless of the legal or non-legal profit, Management has the freedom to change one method to another. The ability to use accounting techniques in records has been proven to be misused by management to make income smoothing.There is an indication of income smoothing in manufacturing companies listed on the BEI, because of 53 companies studied 21 companies do practice income smoothing, only ROA variables that significantly partially affect the income smoothing, while the variable Net profit margin does not significantly influence partially to the alignment profit